Kapasitas Total Antioksidan dan Uji Toksisitas Ekstrak Bunga Kecombrang (Etlingera elatior (Jack) R.M.Sm) - Faiz Agung Hermawan; Frans Ferdinal (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Oxidative stress is imbalance between antioxidant production and the formation of free radicals, which are involved in the development of degenerative diseases. Declining organ function is a symptom of degenerative diseases. The antioxidant helps protect the body from free radicals and prevent oxidative stress. Antioksidan classified into exogenous and endogenous. (Etlingera elatior (Jack) R.M.Sm) flower is known for its antioxidants. This study aimed to establish the toxicity and antioxidant features of kecombrang flower. Total antioxidant capacity test by Blois 1,1 Diphenyl-2Picryhydrazyl  (DPPH) method, toxicity test by Brine Shrimp Lethality Test (BSLT) method. After acquiring simplicia by grinding and aerating the flowers, the extract was obtained by the maceration process using methanol as the solvent and evaporation. The extract was then analyzed. The total antioxidant capacity test showed an IC50 of 931.53 g/mL, indicating that kecombrang flower has a low total antioxidant capacity. Based on the results of the toxicology tests, the LC50 value for the kecombrang flower extract was 612.66 g/mL, indicating that it possessed toxic properties. This study concluded that kecombrang flower extract was shown to have low antioxidant levels and potential antimitotic activity.